Foam roller exercises - Woodworth, Sam (Dorling Kindersley Limited, 2017)
Foam rollers have become a staple of the home gym, and are a trusted tool to avoid injury and aid recovery. Foam Roller Exercises shows you how to make the most of this simple tool with restorative exercises to build core strength, relieve pain, and stretch your muscles. Add foam rolling to your routine and let your body reap the benefits.